Egg-Phosphatidylcholine Attenuates T-Cell Dysfunction in High-Fat Diet Fed Male Wistar Rats - Azarcoya-Barrera, Jessy; Wollin, Bethany; Veida-Silva, Hellen; Makarowski, Alexander; Goruk, Susan; Field, Catherine J.; Jacobs, René L.; Richard, Caroline (Frontiers in Nutrition, 2022)
Obesity is associated with immune dysfunction including an impaired T cell function characterized by a lower IL-2 (proliferation marker) production after stimulation. Phosphatidylcholine (PC, a form of choline mostly found in eggs, has been shown to beneficially modulate T cell responses during the lactation period by increasing the production of IL-2. To determine the impact of egg-PC as part of a high-fat diet on immune function we randomly fed male Wistar rats one of three diets containing the same amount of total choline but differing in the forms of choline: 1- Control low fat (CLF, 10% wt/wt fat, 100% free choline (FC)); 2- Control high-fat (CHF, 25% wt/wt fat, 100% FC); 3- PC high-fat (PCHF, 25% wt/wt, 100% PC). After 9 weeks of feeding, rats were euthanized. Cell phenotypes and ex vivo cytokine production by splenocytes stimulated with phorbol 12-myristate 13-acetate plus ionomycin (PMA+I) and pokeweed (PWM) were measured by flow cytometry and ELISA, respectively. Rats fed the PCHF diet had a lower proportion of CD3+ cells when compared to both the CLF and the CHF. Following PMA+I stimulation, splenocytes from the CHF group produced less IL-2 and TNF-α compared to CLF and PCHF groups. No significant differences in cytokine production were found among groups after LPS and PWM stimulation. Our results show that feeding a high-fat diet impairs T cell responses, as measured by ex vivo cytokine production, which can be attenuated by providing egg-PC.